Rethinking Assets in Islamic Law: Understanding the Logic of Camels as Authorized-Value in Socio-Economic Context - Landy Trisna Abdurrahman; Ahmad Yani Anshori; Moh. Tamtowi; Asmara Edo Kusuma; Muhammad Farhan Burhanudin (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: Early Islamic legal tradition reveals the recurrent appearance of camels in a range of normative provisions, including diyāt (blood money), livestock zakat, sacrifice, and dowry. This pattern has often been read literally as the final legal designation of a specific object, thereby obscuring the relationship between normative texts and the socio-economic context of classical Arab society. This article demonstrates that the prominence of camels did not derive from any intrinsic theological quality, but rather from their socio-economic and symbolic status as the most valuable asset of the time. By reading hadith as part of a discursive tradition, camels are understood as a medium of value that integrates productive economic functions, mobility as moving capital, survival in a desert environment, and symbols of social status and honor. An analysis of clusters of hadith concerning diyāt, zakat, sacrifice, and dowry reveals a consistent logic of value, namely the articulation of obligations and compensations through wealth that was socially recognized as the highest surplus. These practices were subsequently adopted and rationalized in the construction of early fiqh through mechanisms of selection, taqwīm (legal valuation), and the stabilization of norms by the fuqahāʾ. The principal novelty of this article lies in the formulation of an analytical framework that shifts the focus of fiqh from the material form of objects to the functional logic of assets, positioning the social authorization of value as the foundation of legal normativity. This finding has significant implications for fiqh al-muʿāmalāt and contemporary Islamic jurisprudence more broadly, as it provides a methodological basis for evaluating modern assets (unknown in the classical turāth) according to the logics and criteria of māl, including economic utility, capacity for possession, recognition by ʿurf, and rational valuation, without resorting to reductive form-based analogies. Abstrak: Tradisi hukum Islam awal memperlihatkan kemunculan unta secara berulang dalam berbagai ketentuan normatif, seperti diyat, zakat ternak, kurban, dan mahar. Pola ini kerap dibaca secara literal sebagai penetapan objek hukum yang bersifat final, sehingga mengaburkan relasi antara teks normatif dan konteks sosial-ekonomi masyarakat Arab klasik. Artikel ini menunjukkan bahwa dominasi unta tidak bersumber dari kualitas teologis intrinsik objeknya, melainkan dari kedudukan sosial-ekonomi dan simboliknya sebagai aset paling bernilai pada masa itu. Melalui pembacaan hadis sebagai bagian dari tradisi diskursif, unta dipahami sebagai medium nilai yang menautkan fungsi ekonomi produktif, mobilitas sebagai modal yang bergerak, peran bertahan hidup di wilayah gurun, serta simbol status dan kehormatan sosial. Analisis terhadap klaster hadis diyat, zakat, kurban, dan mahar memperlihatkan konsistensi logika nilai, yakni penetapan kewajiban dan kompensasi melalui harta yang secara sosial diakui sebagai surplus tertinggi. Praktik-praktik tersebut kemudian diadopsi dan dirasionalisasi dalam konstruksi fikih awal melalui mekanisme seleksi, taqwīm (legal valuation), dan stabilisasi norma oleh para fuqahāʾ. Kebaruan utama artikel ini terletak pada perumusan kerangka analitis yang menggeser fokus fikih dari bentuk objek ke fungsi aset, dengan menempatkan otorisasi nilai sosial sebagai dasar normativitas hukum. Temuan ini berpengaruh langsung pada pengembangan fikih muamalat dan fikih kontemporer secara umum, karena menyediakan landasan metodologis untuk menilai aset modern (yang tidak dikenal dalam turās) berdasarkan logika dan kriteria māl berupa manfaat ekonomi, kemampuan penguasaan, pengakuan ʿurf, dan rasionalitas nilai, tanpa terjebak pada analogi formal yang reduksionis.